The effect of vertebral artery hypoplasia in posterior circulation infarction in young patients. (1st December 2016) - Yang, Jing; Shen, Zhenglin; Wen, Hongbin; Zhou, Hongbin; Li, Chengyan
Abstract : Purpose Vertebral artery hypoplasia (VAH) is prevalent in the asymptomatic population and contributes to posterior circulation ischaemic events. The aims of this study were to determine whether VAH is an independent risk factor for posterior circulation infarction (PCI) stroke in young patients and to evaluate its impact on the clinical prognosis of PCI stroke in young patients. Materials and Methods The medical records of 235 young stroke patients were reviewed retrospectively. All patients underwent digital subtraction angiography (DSA). VAH was defined by a diameter of <2 mm or the absence of the lateral vertebral artery on DSA. Logistic regression analyses were performed to elucidate the independent factors associated with PCI stroke in young patients. Then, an independent two-sample t -test was performed to evaluate the clinical effect of VAH. Results Our study included 235 young patients who experienced acute ischaemic stroke, 64 of whom were diagnosed with PCI stroke and 38 of whom (16.2%) were found to have VAH. The multivariate logistic regression analysis indicated that gender and VAH were independent risk factors for PCI stroke in young patients. The independent two-sample t -test showed that among the young patients who experienced PCI stroke, the National Institute of Health Stroke Scale score was not significantly different between the patients with and without VAH. Conclusions Our study showed that VAH increases the risk of PCI stroke in young patients. However, the influence of VAH on clinical outcomes in young patients following PCI stroke is minor.